MAKNA RITUS DALAM TARI TOPENG CIREBON - Theguh (Jurnal Budaya Nusantara, 2021)
The role of the mask has always been related to the socio-cultural life of a society. Mask art is a type of folk art. All people can dance mask art as a form to preserve and maintain the artistic heritage of their ancestors. The basis of this research is to reveal the meaning of a Cirebon mask dance symbol. In this research, the method used is descriptive qualitative as an effort to describe and analyze a phenomenon. From this research, it can be concluded that the Cirebon Mask Dance, which is a symbol of the manifestation (representation) of its supporting community, which is displayed in art performances is not just entertainment but has meaning, aesthetics, visual power, and dynamics of motion in its music.